AGAMA BAHA’I PROBLEMATIKA PELAYANAN HAK-HAK SIPIL - Kustini Kustini; Syaiful Arif (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
In the eyes of the law, the Baha’i religion does not exist in this country, as it is not included in the six religions recognized in Indonesia’s constitution: Islam, Protestantism, Catholicism, Hinduism, Buddhism and Confucianism. As a result, it is considered an “unofficial “ or “unrecognized “ religion. In fact, in Article 29 Paragraph 2 of the 1945 Constitution and Article 1 of Law No. 1 / PNPS / 1965, the term “unofficial” and “unrecognized” religion is not even used. The only term used are “followed and serviced” religions. From this perspective, Baha’i is not considered an independent religion, but a splinter group of other religions. This given rise to systemic losses, i.e the unfulfilled civil rights of Baha’is, as part of Indonesian citizens who actually entitled to rights.